2017
DOI: 10.1007/s00401-017-1742-6
|View full text |Cite
|
Sign up to set email alerts
|

The enteric nervous system is a potential autoimmune target in multiple sclerosis

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS) in young adults that has serious negative socioeconomic effects. In addition to symptoms caused by CNS pathology, the majority of MS patients frequently exhibit gastrointestinal dysfunction, which was previously either explained by the presence of spinal cord lesions or not directly linked to the autoimmune etiology of the disease. Here, we studied the enteric nervous system (ENS) in a B cell- and antibody-dependent mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…Also, organ bath functional assays with IgG from patients with systemic sclerosis and Sjögren's syndrome demonstrated an inhibitory antibody effect on M3‐muscarinic receptor agonist‐evoked colonic smooth muscle contraction . A recent study discussed the role of anti‐ENS antibodies in patients with multiple sclerosis, possibly linking GI dysfunction with antibody‐mediated ENS degeneration …”
Section: Discussionmentioning
confidence: 99%
“…Also, organ bath functional assays with IgG from patients with systemic sclerosis and Sjögren's syndrome demonstrated an inhibitory antibody effect on M3‐muscarinic receptor agonist‐evoked colonic smooth muscle contraction . A recent study discussed the role of anti‐ENS antibodies in patients with multiple sclerosis, possibly linking GI dysfunction with antibody‐mediated ENS degeneration …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent work in animal models of MS has demonstrated that the enteric nervous system (ENS), where myelination is minimal, may be a target of autoimmunity in MS. Notably, ENS degeneration occurred in murine models prior to central nervous system (CNS) plaque formation, the pathophysiologic and radiologic hallmark of MS . Moreover, objective GI alterations were observed throughout the gut in animal models without any CNS spinal cord involvement, suggesting ENS dysfunction as the cause .…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between the gut and the central nervous system and its role with other neurodegenerative diseases has been re- Additionally, recent work in animal models of MS has demonstrated that the enteric nervous system (ENS), where myelination is minimal, may be a target of autoimmunity in MS. Notably, ENS degeneration occurred in murine models prior to central nervous system (CNS) plaque formation, the pathophysiologic and radiologic hallmark of MS. 27 Moreover, objective GI alterations were observed throughout the gut in animal models without any CNS spinal cord involvement, suggesting ENS dysfunction as the cause. 27,28 Such a connection between early ENS dysfunction and subsequent development of MS may reflect the increasingly recognized interplay between gut microbiota, permeability of the GI tract, and the enteric neuro-inflammatory pathway.…”
Section: Post-cis Gimentioning
confidence: 99%
See 1 more Smart Citation
“…GI pathologies were previously thought to be primarily explained by spinal cord lesions causing dysfunction of the autonomous nervous system. However, recently it has been suggested that the autoimmune process, which attacks the CNS, directly affects the ENS (Wunsch et al, 2017). In a mouse model of MS called experimental autoimmune encephalomyelitis (EAE), macrophages and T-and B-lymphocytes were observed in the myenteric plexus of the gut, even in the preclinical state.…”
Section: Transmittermentioning
confidence: 99%